2019
DOI: 10.3390/molecules24142618
|View full text |Cite
|
Sign up to set email alerts
|

Detection of 13 Ginsenosides (Rb1, Rb2, Rc, Rd, Re, Rf, Rg1, Rg3, Rh2, F1, Compound K, 20(S)-Protopanaxadiol, and 20(S)-Protopanaxatriol) in Human Plasma and Application of the Analytical Method to Human Pharmacokinetic Studies Following Two Week-Repeated Administration of Red Ginseng Extract

Abstract: We aimed to develop a sensitive method for detecting 13 ginsenosides using liquid chromatography–tandem mass spectrometry and to apply this method to pharmacokinetic studies in human following repeated oral administration of red ginseng extract. The chromatograms of Rb1, Rb2, Rc, Rd, Re, Rf, Rg1, Rg3, Rh2, F1, compound K (CK), protopanaxadiol (PPD), and protopanaxatriol (PPT) in human plasma were well separated. The calibration curve range for 13 ginsenosides was 0.5–200 ng/mL and the lower limit of quantitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 24 publications
1
55
0
Order By: Relevance
“…We used ox-LDL stimulated HUVECs to simulate the occurrence of early atherosclerosis and the healing ability of HUVECs was weakened, notably, the quantity of monocyte adhesion to endothelial cells significantly increased, and Rg3 significantly enhanced healing ability and inhibited monocyte adhesion to HUVECs stimulated with ox-LDL. According to Fan's study (Fan et al, 2016), they reported that the C max of Rg3 reached approximately 100 mmol/L in normal rats plasma after a single oral administration of Rg3, while that of tumor bearing rats was close to 46 mmol/L, indicating that it is possible for physiological concentration of Rg3 after oral administration to reach the higher concentration of Rg3 (30 mmol/L) applied in our study in vitro; meanwhile, in Jin's recently pharmacokinetic studies (Jin et al, 2019), Rg3 was detected as one of the 13 major ginsenosides in human plasma after repeated oral administration of red ginseng extract for two weeks, the daily intake amount of Rg3 from red ginseng extract was 7.9 mg/day, and the C max of Rg3 in human plasma reached 8.7 ng/ml (approximately equal to 13 mmol/L) which is close to our lower concentration of Rg3 (15 mmol/L), suggesting that the concentration of Rg3 we used in vitro is significant for the study of Rg3 pharmacology. Investigations have shown that Rg3 can reverse the M1 polarization to the M2 phenotype in diabetic conditions to repress the occurrence of diabetes-complicated atherosclerosis (Guo et al, 2018), our further experiments confirmed that HFD for 12 weeks lead to plenty of atherosclerotic plaque formation in aorta of ApoE −/− mice, accompanied by abnormal lipoprotein profiles in serum, while Rg3 decreased LDL level and increased HDL level in serum of ApoE −/− mice, inhibited atherosclerotic plaque formation obviously.…”
Section: Discussionsupporting
confidence: 50%
“…We used ox-LDL stimulated HUVECs to simulate the occurrence of early atherosclerosis and the healing ability of HUVECs was weakened, notably, the quantity of monocyte adhesion to endothelial cells significantly increased, and Rg3 significantly enhanced healing ability and inhibited monocyte adhesion to HUVECs stimulated with ox-LDL. According to Fan's study (Fan et al, 2016), they reported that the C max of Rg3 reached approximately 100 mmol/L in normal rats plasma after a single oral administration of Rg3, while that of tumor bearing rats was close to 46 mmol/L, indicating that it is possible for physiological concentration of Rg3 after oral administration to reach the higher concentration of Rg3 (30 mmol/L) applied in our study in vitro; meanwhile, in Jin's recently pharmacokinetic studies (Jin et al, 2019), Rg3 was detected as one of the 13 major ginsenosides in human plasma after repeated oral administration of red ginseng extract for two weeks, the daily intake amount of Rg3 from red ginseng extract was 7.9 mg/day, and the C max of Rg3 in human plasma reached 8.7 ng/ml (approximately equal to 13 mmol/L) which is close to our lower concentration of Rg3 (15 mmol/L), suggesting that the concentration of Rg3 we used in vitro is significant for the study of Rg3 pharmacology. Investigations have shown that Rg3 can reverse the M1 polarization to the M2 phenotype in diabetic conditions to repress the occurrence of diabetes-complicated atherosclerosis (Guo et al, 2018), our further experiments confirmed that HFD for 12 weeks lead to plenty of atherosclerotic plaque formation in aorta of ApoE −/− mice, accompanied by abnormal lipoprotein profiles in serum, while Rg3 decreased LDL level and increased HDL level in serum of ApoE −/− mice, inhibited atherosclerotic plaque formation obviously.…”
Section: Discussionsupporting
confidence: 50%
“…Among PPD-type ginsenosides that inhibited in vitro OATP function, ginsenosides Rb1, Rb2, and Rc demonstrated high affinity for OATP1B3 inhibition (1.9-5.1 µM for OATP1B3; Figure 7). However, the maximum plasma concentrations (C max ) of Rb1, Rb2, and Rc in rats were in the range of 5.3-15.8 nM following repeated administration of RGE (1.5 g/kg/day) for 7 days ( Figure 6) and C max of Rb1, Rb2, and Rc in human were 6.2-12.7 nM following repeated administration of RGE (3 g/day) for 14 days [31]. The selected RGE dose in this study is in the range of effective dose without significant toxicity and showed similar plasma concentrations of Rb1, Rb2, and Rc (5.3-15.8 nM in rats and 6.2-12.7 nM in human subjects) [19,33].…”
Section: Discussionmentioning
confidence: 98%
“…To explain the lack of herb-drug interaction between RGE and valsartan, we measured the plasma concentrations of ginsenosides following repeated administration of RGE using the previously developed analytical method by LC-MS/MS [19,31]. Among the 14 ginsenosides examined (Rb1, Rb2, Rc, Rd, Rh2, Rg3, F2, compound K, PPD, Re, Rh1, Rg1, F1, and PPT), 6 ginsenosides were detected in the plasma samples and the plasma concentrations of the 6 ginsenosides are shown in Figure 6.…”
Section: Effect Of Rge On the Pharmacokinetics Of Valsartan In Ratsmentioning
confidence: 99%
See 2 more Smart Citations